Guide to dataflow supercomputing : basic concepts, case studies, and a detailed example /: basic concepts, case studies, and a detailed example. ([2015]) - Milutinović, Veljko; Salom, Jakob; Trifunović, Nemanja; (Computer engineer), Giorgi, Roberto
No abstract available